The use of growth promoters in swine nutrition: Problems and perspectives concerning public health and swine production - TZIKA (Ε. Δ. ΤΖΗΚΑ) E. D.; SBIRAKI (Α.Π. ΣΜΠΙΡΑΚΗ) A. P.; KRITAS (Σ. Κ. ΚΡΗΤΑΣ) S. K.; KOUTSOVITI - PAPADOPOULOU (Μ. ΚΟΥΤΣΟΒΙΤΗ-ΠΑΠΑΔΟΠΟΥΛΟΥ) M.; KYRIAKIS (Σ.K. ΚΥΡΙΑΚΗΣ) S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
The use of antimicrobial agents as growth promoters is widely established in modern commercial units, in order to improve and increase the animal production. Based on the controversy of the use of avoparcin which arose the last two years, as well as with spiramycin, tylosin, zinc-bacitracin and virginiamycin the past year, the use of antimicrobial agents is under severe criticism. Several scientific organizations are supportive to the ban of the use of antimicrobial agents as feed additives. The objections refer to the toxicity of some growth promoters, their lower effects under optimized housing conditions, as well as to the mode of application without veterinary prescription. Moreover, they refer to their possible incompatibility with other therapeutics, the hazard of residues in animal origin food, the intoxications in nontarget species such as ionophores in horses and especially the hazard of development of resistance in bacteria. The purpose of this paper is to present the advantages and disadvantages of the in-feed use of antimicrobial agents as growth promoters, especially in swine, which along with poultry represent the main categories of productive animals where an extended use of such pharmaceuticals is applied. Finally, some proposals are being mentioned emphasizing on the need for veterinary control of all antimicrobial agents, including the growth promoters, which are used in animals (predisposing that their application is under veterinary prescription).